Notch and Bmp signaling pathways act coordinately during the formation of the proepicardium. Issue 12 (3rd September 2020) - Andrés‐Delgado, Laura; Galardi‐Castilla, María; Münch, Juliane; Peralta, Marina; Ernst, Alexander; González‐Rosa, Juan Manuel; Tessadori, Federico; Santamaría, Luis; Bakkers, Jeroen; Vermot, Julien; de la Pompa, José Luis; Mercader, Nadia
Abstract: Background: The epicardium is the outer mesothelial layer of the heart. It encloses the myocardium and plays key roles in heart development and regeneration. It derives from the proepicardium (PE), cell clusters that appear in the dorsal pericardium (DP) close to the atrioventricular canal and the venous pole of the heart, and are released into the pericardial cavity. PE cells are advected around the beating heart until they attach to the myocardium. Bmp and Notch signaling influence PE formation, but it is unclear how both signaling pathways interact during this process in the zebrafish. Results: Here, we show that the developing PE is influenced by Notch signaling derived from the endothelium. Overexpression of the intracellular receptor of notch in the endothelium enhances bmp expression, increases the number of pSmad1/5 positive cells in the DP and PE, and enhances PE formation. On the contrary, pharmacological inhibition of Notch1 impairs PE formation. bmp2b overexpression can rescue loss of PE formation in the presence of a Notch1 inhibitor, but Notch gain‐of‐function could not recover PE formation in the absence of Bmp signaling. Conclusions: Endothelial Notch signaling activates bmp expression in the heart tube, which in turn induces PE cluster formation from the DP layer. Key Findings: Notch is active on endothelial cells but not on EPDCs cells during PE formation. Endothelial Notch signaling activates Bmp expression in the heart‐tube. Notch and Bmp pathways induce PE cluster formation from the DP layer.